Identification and Characterization of Fusarium Species Causing Watermelon Fruit Rot in Northern Thailand - Wipornpan Nuangmek; Jaturong Kumla; Surapong Khuna; Saisamorn Lumyong; Nakarin Suwannarach (Plants, 2023)
Fruit rot caused by phytopathogenic fungi is one of the major diseases affecting watermelons (Citrullus lanatus) around the world, which can result in unmarketable fruits and significant economic losses. Fruit rot was observed on watermelons throughout the postharvest storage periods in Phayao Province, northern Thailand in 2022. For the present study, a total of ten fungal isolates were isolated from the rot lesions of watermelons. All obtained fungal isolates were then characterized in terms of their pathogenicity. The results indicated that only four fungal isolates caused rot disease with similar symptoms during the postharvest storage period. Based on their morphological characteristics, these four fungal isolates were identified as belonging to the genus Fusarium. Using multi-gene phylogenetic analyses with a combination of the translation elongation factor 1-alpha (tef-1), calmodulin (cam), and RNA polymerase second largest subunit (rpb2) genes, the fungal isolates were subsequently identified as Fusarium compactum and F. paranaense. Taken together, the results of this study indicate that F. compactum and F. paranaense cause fruit rot disease in watermelons. To the best of our knowledge, this is the first study to report F. compactum and F. paranaense as novel pathogens of watermelon fruit rot both in Thailand and elsewhere in the world.